Comparative Study Between Usg Guided Aspiration And Incision And Drainaige In Breast Abscess. (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Breast abscess is defined as an acute inflammatory lump frequency of occurrence  is highly related to pregnancy and caused due to nipple piercing by a child during feeding and  bacterial colonization due to improper nursing technique and incomplete emptying of the  breast.The present study compares the outcome and effectiveness of traditional treatment  incision and drainage against needle aspiration in the treatment of breast abscess. Methods: This is a comparative study carried out in department of general surgery,smt SCL HOSPITAL, affliated with s.m.t.N.H.L.Medical college,AHMEDABAD for a period of 1 years (june  2018 – may 2019). 50 female patients of age between 18-45 years were included in the study  after taking written consent form. Of these 28 had undergone usg guided aspiration of the breast abscess (group A) and 22 had undergone incision and drainage of the breast abscess  (groupB).  Results: The mean age of the female patients in the study were 23.9years.The mean healing  time and cosmetic outcome was significantly very good in patients treated with needle  aspiration compared to incision and drainage. Conclusions: Breast abscess in patients with diameter of less than 5cm can be treated with  needle aspiration successfully and with a good cosmetic outcome.
Keywords: Needle aspiration; Incision and drainage; Breast abscess